Blood microRNAs as potential diagnostic and prognostic markers in cerebral ischemic injury - Bridget Martinez; Philip V Peplow (Neural Regeneration Research, 2016)
MicroRNAs are a family of small, genome-encoded endogenous RNAs that are transcribed but are not translated into proteins. They serve essential roles in virtually every aspect of brain function, including neurogenesis, neural development, and cellular responses leading to changes in synaptic plasticity. They are also implicated in neurodegeneration and neurological disorders, in responses to hypoxia and ischemia, and in ischemic tolerance induced by ischemic preconditioning. In recent developments, miRNA expression profiling has been examined in stroke, and these studies indicate that miRNAs have emerged as key mediators in ischemic stroke biology. Both increased and decreased miRNA levels may be needed either as prevention or treatment of stroke. Novel approaches are being developed to get miRNA related therapeutics into the brain across an intact blood-brain barrier, including chemical modification, use of targeting molecules and methods to disrupt the blood-brain barrier.